Overexpression of StTCP10 Alters Tuber Number and Size in Potato (Solanum tuberosum L.) - Tingting Wang; Xinyue Chen; Shuangshuang Li; Ping Wang; Yongbin Wang; Binquan Huang (Plants)
Potato (Solanum tuberosum L.), cultivated worldwide for its nutrient-rich underground tubers, represents a crucial staple crop whose yield is primarily determined by both tuber number and tuber size. TCP transcription factors, especially TCP containing miR319 binding sites, play pivotal roles in plant growth and development, yet their functions in potato tuber number and size remain largely unexplored. In this study, we systematically identified 32 TCP genes in potato harboring the conserved TCP domain, among which six were predicted to contain binding sites for Stu-miR319. Semi-quantitative experiments revealed that StTCP10 exhibited the highest expression levels in stolons, swollen stolons, and tuber tissues compared to other StTCP genes containing miR319 binding sites. To elucidate its biological function, we generated StTCP10-overexpressing transgenic potato lines through Agrobacterium-mediated genetic transformation. Phenotypic analysis demonstrated that overexpression of StTCP10 reduced tuber number per plant while enhancing tuber size, with no significant change in total yield. These findings reveal that StTCP10 with Stu-miR319 binding sites plays a critical role in tuber size and mediates the trade-off between tuber size and number, providing novel insights into the molecular breeding aimed at improving tuber size.